Some diverse examples of exploiting the beneficial effects of geometric stiffness nonlinearity - Gatti, G. (2019)
The effects of nonlinearity, particularly stiffness nonlinearity, has been of concern to structural engineers for many years. The main reason for this is because this type of nonlinearity can cause unpredictable dynamics, and considerable effort is necessary to analyse nonlinear structures. However, due to the recent computational advances, and the continuous need to improve the performance and efficiency of structures and mechanical devices, engineers have recently started to investigate whether nonlinearity can be incorporated into structures to provide some benefit. This paper presents four case-studies where this type of nonlinearity can be introduced to good use. The required nonlinear stiffness varies from case to case, but can be realised in each case with a simple geometric arrangement of up to three linear springs. The case-studies involving vibration isolators, vibration neutralizers, vibration energy harvesters and micro-air-vehicles are discussed in this context.